Heat Utilization of Incinerator Chimney as Mini Power Generator Based on Thermoelectric - Usman Syamsuddin; Zulkifli Djafar; Thomas Tjandinegara; Zuryati Djafar; Wahyu Haryadi Piarah (EPI International Journal of Engineering, 2018)
The thermoelectric generator (TEG) has long been used to produce electrical energy where when a temperature difference occurs between two different semiconductor materials, this thermoelectric element will produce a voltage difference and flow an electric current. This principle is known as the 'Seebeck effect'. This research was conducted to determine the electrical energy potential of the TEG module as an alternative energy source by utilizing chimney heat from an incinerator. The test was carried out with a variation of 1, 2 and 3 m chimney height with treatment without compaction and compaction of waste. The test results show that with 12 TEG modules arranged in series electricity can produce an output voltage with a maximum temperature difference of each ΔV 3,31 Volt ; ΔT 15,0 °C (1 m), ΔV 3,92 Volt; ΔT 17,8 °C (2 m), ΔV 4,84 Volt ; ΔT 22,0 °C (3 m) while the compaction of each value ΔV 6,34 Volt ; ΔT 29,2 °C (1 m), ΔV 7,69 Volt ; ΔT 35,2 °C (2 m), ΔV 9,09 Volt ; ΔT 41,5 °C (3 m). The potential power that can be produced is as big as 3,22 W (1 m); 4,56 W (2 m); 6,88 W (3 m) while the compaction of waste is equal to each value 11,80 W (1 m); 17,36 W (2 m); 24,25 W (3 m). The addition of chimney height variation resulted in an increase in the hot side temperature (Th), cold side (Tc) and temperature difference (dT) so that heat energy and power energy increased.